Cytotoxic Evaluation of Medicinal Plants used by Suku Anak Dalam Community in Jambi Province Using the Brine Shrimp Lethality Test - Santi Perawati; Nurul Kamilah Sadli; Marizki Pondawinata; Rina Oktaria; Lili Andriani; Diah Kusumawati; Evelin Sabatini Sinaga; Fauziyah (Indonesian Journal of Chemical Studies, 2026)
Cancer remains a major global health challenge, and the search for effective therapeutic agents continues. Natural products, including traditional medicinal plants used by the Suku Anak Dalam (SAD) community in Jambi, offer promising sources of bioactive compounds. This study investigated the cytotoxic potential of ten SAD medicinal plants extracted through a decoction method. Phytochemical screening revealed the presence of alkaloids, flavonoids, and saponins. Cytotoxicity was assessed using the Brine Shrimp Lethality Test (BSLT) at concentrations of 50, 100, 500, and 1000 ppm. All plant extracts exhibited toxic-level cytotoxicity, which correlated with their secondary metabolite profiles and their inhibitory effects on Artemia salina Leach larvae. The LC₅₀ values ranged from 150 to 400 ppm, indicating that these traditional medicinal plants possess notable cytotoxic activity. These findings support the potential of SAD ethnomedicinal plants as candidates for further investigation in anticancer research.